Efficacy and health economics of Bufei Yishen granules in patients with frequent exacerbator phenotype in the stable phase of chronic obstructive pulmonary disease: study protocol for a multicenter, randomized, double-blind, placebo-controlled trial - Xiao, Qionghua; Wang, Minghang; Li, Zegeng; Chen, Tao; Li, Jiansheng (Frontiers in Medicine, 2025)
IntroductionPatients with frequent exacerbator phenotype in chronic obstructive pulmonary disease (COPD) tend to experience a progressive decline in lung function, a gradual deterioration of the disease, and even a serious threat to their lives. However, current treatment measures still need further improvements to reduce the frequency of acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Therefore, our team developed Bufei Yishen (BFYS) granules specifically for patients with frequent exacerbator phenotype in COPD and is conducting a randomized controlled trial (RCT) to validate their effectiveness.MethodsA multi-center, randomized, double-blind, placebo-controlled trial will be conducted. A total of 848 patients will participate in the study, with a treatment duration of 1 year. The participants will be randomly assigned to the experimental group and the control group in a 1:1 ratio. Both groups will receive health education and conventional drugs. In addition, the experimental group will receive BFYS granules, while the control group will be given the corresponding BFYS placebo. The primary outcome is the frequency of AECOPD. The secondary outcomes include the frequency of AECOPD leading to hospitalization, the mortality rate, lung function, six-minute walk distance (6MWD), clinical symptoms and signs scores, and quality of life. Safety outcomes include vital signs and laboratory tests. Statistical analysis will be conducted using SPSS software (version 25.0). Furthermore, the health economics evaluation of the BFYS granules will use cost-effectiveness analysis methods.Ethics and disseminationThe study protocol was approved by the Ethics Committee of the First Affiliated Hospital of Henan University of Chinese Medicine (No. 2024HL-043-01). Written informed consent will be obtained from all participants. The results will be published in a peer-reviewed journal after the end of the study. The data of this trial will be disseminated publicly through conferences and publications.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06326658.